2015
DOI: 10.1007/s12571-015-0533-y
|View full text |Cite
|
Sign up to set email alerts
|

The role and challenges of new diagnostic technology in plant biosecurity

Abstract: Pest and pathogens pose a major threat to food security and the natural environment, and these threats are moving around the globe. Trade, travel and transport have major roles to play in this and thus to improve plant biosecurity, we need enhanced phytosanitary inspection systems. In order to achieve this, there is a role for the more effective use of diagnostic technology, such as field-based testing or the use of next generation sequencing technology. In this review we examine the opportunities and challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 33 publications
0
34
0
1
Order By: Relevance
“…Early work has indicated that some of these viruses are prevalent and may protect the infected plants from adverse environmental conditions such as temperature or drought (Roossinck 2013). In the short term however, the presence of these viruses or of uncharacterised viruses may pose potentially significant technical and policy related challenges for plant health risk management (Macdiarmid et al 2013;Mumford et al 2016;Massart et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Early work has indicated that some of these viruses are prevalent and may protect the infected plants from adverse environmental conditions such as temperature or drought (Roossinck 2013). In the short term however, the presence of these viruses or of uncharacterised viruses may pose potentially significant technical and policy related challenges for plant health risk management (Macdiarmid et al 2013;Mumford et al 2016;Massart et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Plant pests and pathogens have an important role in global food crops causing significant economic losses in the agricultural industry and threatening food security [ [1] , [2] , [3] ]. Yam ( Dioscorea spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Historic data suggest a strong influence of human activity on the dissemination of viruses through trade and transportation of infected plant material [ 1 , [19] , [20] , [21] ]. Applying full phytosanitary surveillance in plant quarantine and certification facilities is unrealistic due to high costs associated with increasing inspection rates [ 3 ]. Therefore, there is an urgent need to develop improved detection methods for yam viruses to help make timely decisions on the health status of yam planting material.…”
Section: Introductionmentioning
confidence: 99%
“…Plant pests and diseases, both invasive and native, represent a major threat to plant biosecurity globally Mumford, Macarthur and Boonham, 2016;Brasier, 2008), and present policy and management challenges to the international community. These organisms have degraded ecosystems and impacted endemic species (Mumford, Macarthur and Boonham, 2016). Acute Oak Decline (AOD) threatens native oaks in Great Britain (Denman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%